2020
DOI: 10.1038/s41467-019-13968-8
|View full text |Cite
|
Sign up to set email alerts
|

Topological magneto-optical effects and their quantization in noncoplanar antiferromagnets

Abstract: Magneto-optical (MO) effects have been known for more than a century as they reflect the basic interactions between light and magnetism. The origin of MO effects is usually ascribed to the simultaneous presence of band exchange splitting and spin-orbit coupling. Using a tight-binding model and first-principles calculations, we show that topological MO effects, in analogy to the topological Hall effect, can arise in noncoplanar antiferromagnets entirely due to the scalar spin chirality instead of spin-orbit cou… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
48
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 74 publications
(49 citation statements)
references
References 65 publications
(54 reference statements)
1
48
0
Order By: Relevance
“…In addition to these coplanar antiferromagnetic metals, Feng et al recently identified compensated non-coplanar orderings as candidates for strong MOKE signals and illustrate this using first-principles results for Kerr rotation angles of γ-Fe 0.5 Mn 0.5 . 174 Most of the above results focus on polar MOKE, i.e., MOKE for surfaces perpendicular to the direction characterizing magnetic ordering, e.g. that of weak magnetization.…”
Section: And 156mentioning
confidence: 99%
“…In addition to these coplanar antiferromagnetic metals, Feng et al recently identified compensated non-coplanar orderings as candidates for strong MOKE signals and illustrate this using first-principles results for Kerr rotation angles of γ-Fe 0.5 Mn 0.5 . 174 Most of the above results focus on polar MOKE, i.e., MOKE for surfaces perpendicular to the direction characterizing magnetic ordering, e.g. that of weak magnetization.…”
Section: And 156mentioning
confidence: 99%
“…Moreover, the noncoplanar spin structures can generate the so-called emergent electromagnetic fields through the Berry phase mechanism [4,24,[28][29][30][31]. They are fictitious electromagnetic fields acting on electrons coupled to the spin textures, and thus, give rise to unusual quantum transport and optical phenomena, such as the topological Hall effect [32][33][34][35][36][37], the Nernst effect [38][39][40], the magneto-optical Kerr effect [41,42], and the emergent inductance [43][44][45][46][47]. Owing to these distinguishing properties, the topological spin textures have attracted a lot of attention for not only fundamental physics but also applications to next-generation electronic devices.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic topological states are currently attracting widespread interest in condensed matter physics with a variety of exotic topological phenomena constantly proposed and intensively explored [1,2], and in which, the anomalous Hall effect [3][4][5][6][7], spin-orbit torques [8], magneto-optical effect [9,10], and Dzyaloshinskii-Moriya interaction [11,12] can exceed by far that of conventional compounds, suggesting a huge potential for spintronic devices. Antiferromagnetic (AFM) topological insulator (TI) [13], a conceptual milestone, has been demonstrated in three-dimensional (3D) MnBi 2n Te 3n+1 (n = 1, 2, 3) family of materials with axion topology and Möbius fermion ensured by a combined symmetry T T 1/2 , where T is the time-reversal symmetry and T 1/2 represents the half primitive-lattice translation [14][15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%